PENGARUH BUDAYA ORGANISASI DAN GAYA KEPEMIMPINAN TERHADAP KINERJA PEGAWAI BAGIAN KEUANGAN ORGANISASI SEKTOR PUBLIK DENGAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING - Arum Alphinia; Dwiyani Sudaryanti; Arista Fauzi Kartika Sari (Universitas Islam Malang, 2020)
ABSTRACTThis study aims to determine how much influence organizational culture and leadership style have on employee performance with work motivation as an intervening variable. In this study, there are 2 independent variables, namely organizational culture and leadership style, one dependent variable, namely employee performance and one mediating variable, namely work motivation. The data used in this study are primary data, the population taken in this study are employees who work in the city government of Banyuwangi. Data collection techniques in this study using purposive sampling method. The test used in this study is the t test, R2 test. The results in this study indicate that partially organizational culture, leadership style and work motivation have a significant effect on stock investment decisions.Keywords: Organizational Culture, Leadership Style, Employee Performance, Work Motivation